Before Australia: Historicising Russian Migration via China after World War II. Issue 1 (2nd January 2019) - Balint, Ruth
Abstract : In 1945, tens of thousands of Russian and Russian-speaking Jewish refugees were in China. Many had come decades earlier, following the Bolshevik revolution, the rout of anti-Bolshevik armies in 1919–20 and the White Russian defeat in Siberia in 1922. At war's end, they became part of the large cohort of European refugees in the Far East, displaced by National Socialism and then by Communism, who urgently sought resettlement in the West. A significant number eventually came to Australia in the late 1940s and early 1950s. Yet, Russian migration to Australia via the China route is poorly understood in the historiography. This article examines Russian migration to China in the first half of the twentieth century, and their departure from China in the late 1940s and 1950s. Their trajectory was complicated first by events in China, and second, by their encounters with the international refugee agencies created by the Allies to assist those displaced by the war.